Transition analysis of flat-foldable origami-inspired deployable shelter concepts. (15th December 2022) - Verzoni, Anthony; Rais-Rohani, Masoud
Graphical abstract: Abstract: Deployable shelters have many applications, including disaster relief and temporary housing. The ability to transport and rapidly erect such shelters is an important design consideration. Inspired by the geometric attributes of origami, multiple rapidly deployable foldable shelter design concepts are presented and analyzed by considering such requirements as (a) flat-foldability, (b) kinematic compatibility, (c) panel connectivity, and (d) load requirement to unfold the shelter completely to its upright position. Both thin- and thick-walled concepts based on consistent and accurate CAD models are evaluated and compared, with thick walls posing additional constraints, including placement of the hinge lines and nesting of panels with varied thicknesses to accommodate flat-foldability. Rigorous mathematical models are developed for transition analysis and determination of the erection torque based on the load location and without causing any panel to experience in-plane or out-of-plane deformation. The analytical solutions are compared to and verified with those obtained through detail CAD modeling and motion simulation with SolidWorks® CAD and SolidWorks Motion. The results show that compound folding patterns can be accommodated in flat-foldable, thick-walled, origami-inspired shelter concepts that act mostly or fully as a single-degree-of-freedom system with maximum connectivity of the shelter panels. Moreover, the erection torque is found to depend strongly on its application location and vary significantly during the transition process. The results reveal the importance of transition analysis and the merits of different concepts for informing future design decisions affecting the size, shape, and erection load for similar deployable shelters.